SDG8-Mediated Histone Methylation and RNA Processing Function in the Response to Nitrate Signaling. Issue 1 (22nd October 2019) - Li, Ying; Brooks, Matthew; Yeoh-Wang, Jenny; McCoy, Rachel M.; Rock, Tara M.; Pasquino, Angelo; Moon, Chang In; Patrick, Ryan M.; Tanurdzic, Milos; Ruffel, Sandrine; Widhalm, Joshua R.; McCombie, W. Richard; et al.
Abstract : Nitrogen nutrient can trigger changes in chromatin modifications, thus affecting RNA processing, metabolism, and growth in plants. Abstract: Chromatin modification has gained increased attention for its role in the regulation of plant responses to environmental changes, but the specific mechanisms and molecular players remain elusive. Here, we show that the Arabidopsis ( Arabidopsis thaliana ) histone methyltransferase SET DOMAIN GROUP8 (SDG8) mediates genome-wide changes in H3K36 methylation at specific genomic loci functionally relevant to nitrate treatments. Moreover, we show that the specific H3K36 methyltransferase encoded by SDG8 is required for canonical RNA processing, and that RNA isoform switching is more prominent in the sdg8-5 deletion mutant than in the wild type. To demonstrate that SDG8-mediated regulation of RNA isoform expression is functionally relevant, we examined a putative regulatory gene, CONSTANS, CO-like, and TOC1 101 ( CCT101 ), whose nitrogen-responsive isoform-specific RNA expression is mediated by SDG8. We show by functional expression in shoot cells that the different RNA isoforms of CCT101 encode distinct regulatory proteins with different effects on genome-wide transcription. We conclude that SDG8 is involved in plant responses to environmental nitrogen supply, affecting multiple gene regulatory processes including genome-wide histone modification, transcriptional regulation, and RNA processing, and thereby mediating developmental and metabolic processes related to nitrogen use.